Design of UV-Vis-NIR panchromatic crown-phthalocyanines with controllable aggregation. Issue 3 (25th November 2014) - Safonova, Evgeniya A.; Martynov, Alexander G.; Zolotarevskii, Viktor I.; Nefedov, Sergey E.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.
Abstract : Novel donor–acceptor phthalocyanines bearing 15-crown-5-oxanthrene fragments are designed and synthesized to expand light absorbance for further optoelectronic applications. Abstract : Novel magnesium and zinc phthalocyaninates, bearing four lateral electron-rich 15-crown-5-oxanthrene fragments, were synthesized starting from benzo-15-crown-5. Being almost insoluble in common organic solvents, these complexes could be solubilised by interaction with potassium acetate due to the formation of well-defined cofacial supramolecular dimers. A characteristic feature of these dimers is the presence of additional bands in their UV-Vis spectra, which affords the expansion of light absorption region up to ∼750 nm. This new band corresponds to the charge transfer from the peripheral groups to the Pc core, as evidenced by TDDFT calculations. Potassium cations can be reversibly removed from these dimers by [2.2.2]cryptand, resulting in the formation of monodisperse nanoparticles exhibiting absorbances up to 900 nm. This approach can be further used for the fabrication of nanostructured optoelectronic materials based on the synthesized donor–acceptor panchromatic crown-phthalocyanines.